Prática docente e o autismo: as barreiras enfrentadas pelos docentes em suas práticas pedagógicas na E.M.E.I.E.F profª Emília Gimennez, em Castanhal/PA - CORREA, Tassia Juliana dos Santos (2019)
This work, entitled Teaching Practice and Autism: the barriers faced by teachers in their pedagogical practices, investigated the main difficulties faced by teachers, the Emilia Gimennez Municipal School in Castanhal. The study was based on a qualitative approach, to the data collection was used an interview composed of twelve questions, addressed to teachers, mediator and coordinator who had autistic students in the classroom. The data were analyzed based on the authors who have been discussing the inclusion of the autistic student and the training of teachers such as Bosa (2006), Cunha (2014), Mantoan (2015), Silva (2013), Araújo 2003), among others. It was concluded that the greatest difficulty found by teachers is the elaboration of adapted activity, which may be a consequence of the lack of continuous training available by the Municipal Education Network. The study also reveals that most of the time activities end up excluding autistic students because their needs are not adequate. However, even with difficulties, some teachers are always seeking to improve their methodologies to minimize the difficulties of their student, whether in communication, social interaction, reading or writing. However, poor understanding of the majority of teachers ends up affecting the development of their students, which may contribute to the ineffectiveness of the methodologies used in the classroom, which leads us to a reflection about the availability of qualified teachers in the municipality of Castanhal.